Psychotherapy Interventions for Managing Anxiety and Depressive Symptoms in Adult Brain Tumor Patients: A Scoping Review - Kangas, Maria (Frontiers in Oncology, 2015)
Background: Adult brain tumor (BT) patients and longer-term survivors are susceptible to experiencing emotional problems, including anxiety and/or depression disorders, which may further compromise their quality-of-life (QOL) and general well-being. The objective of this paper is to review psychological approaches for managing anxiety and depressive symptoms in adult BT patients. A review of psychological interventions comprising mixed samples of oncology patients, and which included BT patients is also evaluated. The review concludes with an overview of a recently developed transdiagnostic psychotherapy program which was specifically designed to treat anxiety and/or depressive symptoms in adult BT patients. Methods: Electronic databases (PsycINFO, Medline, Embase, and Cochrane) were searched to identify published studies investigating psychological interventions for managing anxiety and depressive symptoms in adult BT patients. Only four randomized controlled trials (RCTs) were identified. Results: Only one of the RCTs tested a psychosocial intervention which was specifically developed for primary BT patients, and which was found to improve QOL including existential well-being as well as reducing depressive symptoms. A second study tested a combined cognitive rehabilitation and problem-solving intervention, although was not found to significantly improve mood or QOL. The remaining two studies tested multidisciplinary psychosocial interventions in heterogeneous samples of cancer patients (included BT patients) with advanced stage disease. Maintenance of QOL was found in both studies, although no secondary gains were found for improvements in mood. Conclusions: There is a notable paucity of psychological interventions for BT patients across the illness trajectory. Further research is required to strengthen the evidence base for psychological interventions in managing anxiety and depressive symptoms and enhancing the QOL of distressed adults diagnosed with a BT.